Reduction of Severe Hypoglycaemia in People with Type 2 Diabetes after a Structured Inpatient Intervention - Kloos, Christof; Burghardt, Katharina; Müller, Ulrich Alfons; Kramer, Guido; Müller, Nicolle; Wolf, Gunter; Kuniss, Nadine (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective The aim of this longitudinal study was to assess outcomes before and one year after participation in a structured inpatient intervention including participation in an education programme for people with type 2 diabetes.Methods In 2014, 81 individuals, who were admitted to optimise insulin therapy, participated in a structured inpatient intervention and were invited to participate in a follow-up visit after one year.Results Seventy participants (46.9% female, age 68.3 y, diabetes duration 17.9 y, HbA1c 9.7%/82.5 mmol/mol) were followed-up after 1.2 y (3 died by non-diabetic causes, 8 declined/were not available). HbA1c decreased by 1.1% (p<0.001) without change of insulin dose (79.7 vs. 79.3 IU, n.s.) or BMI (33.6 vs. 33.8 kg/m2, n.s.). 5 people admitted because of severe hypoglycaemia (one person with 5 episodes and 4 with one episode in the year prior to participation) did not experience another event in the evaluation period, nor did anyone in the rest of the cohort (frequency of severe hypoglycaemia 0.12 events/year before and 0.0 after intervention).Conclusions In people admitted for optimising insulin therapy or severe hypoglycaemia, metabolic control improved substantially and frequency of severe hypoglycaemia was significantly reduced after participation in a structured inpatient intervention. Reasons could be motivational and better adapted eating habits, tailoring individual therapy solutions and deescalating diabetes therapy in people after severe hypoglycaemia.
Keywords: diabetes type 2; diabetes treatment and teaching programme; hypoglycaemia; patient education